PROCEEDINGS OF DIVORCE FOR WOMEN ACCORDING TO FIQH AL-SHAFI'IYYAH AND POSITIVE LAW - Nurdin (Al-Mubin, 2025)
Divorce Delegation for Women According to Fiqh Al-Syafi’iyyah and Positive Law". This study aims to analyze the position of women as recipients of wakalah in the context of divorce, especially in the practice of divorce. In the perspective of Fiqh Al-Syafi’iyyah, divorce is a husband’s prerogative that cannot be delegated to women. However, there are different views among scholars regarding the possibility of women becoming representatives in issuing divorce against another person’s wife. Meanwhile, in positive law, women and men have the same rights to become legal representatives regardless of gender, so that women can represent their husbands in court proceedings. The research method used is descriptive-analytical with a normative-juridical and comparative approach, as well as library research utilizing various sources from fiqh books and laws. The results of the study show that in the perspective of Fiqh Al-Syafi’iyyah, although women do not have the right to divorce, they can act as representatives in some cases with certain provisions. Meanwhile, in positive law, there is no prohibition for women to become legal representatives in divorce cases. The conclusion of this study is that although there are Despite the fundamental differences between Shafi'iyyah Fiqh and positive law, there is a similarity in the recognition of women's rights as representatives in divorce proceedings. This research is expected to contribute to further understanding of women's roles in divorce law and their rights in the Indonesian legal system. Keywords: Wakalah Talak, Shafi'iyyah Fiqh, Positive Law, Women, Divorce.